Teachers' readiness in the teaching of Mathematics and Science in English / Richard Banter - Banter, Richard (2009)
When the Malaysian Education Ministry announced a change in the medium of instruction from the national language, Bahasa Malaysia to English for Mathematics and science subjects for Primary one, form one, and lower sixth forms, beginning the year 2003, teachers and students nationwide have to grapple with the switch of language. As the implementation news was announced at a very short notice, many teachers were caught by surprise as some were not prepared to deliver the subjects using English. This is probably due to lack of proficiencies, confidence and inadequate command of English. These problems, if not taken seriously would undermine the process of teaching and learning and subsequently students would be the victim as they are the ones that sit for the assessment and examination. Therefore,this study using questionnaires is undertaken to investigate the Teachers' Readiness in the Teaching of Mathematics and Science in English. Sixty-nine respondents from four selected secondary schools in Kuching, Sarawak participated in this study. The major finding shows that a large number of the respondents felt that they were ready to teach Mathematics and Science in English. The finding also indicated that the respondents were proficient and confident in teaching both the subjects in English as indicated by 75% or 53 of the respondents. Although, courses and training were given 25% or 16 of the respondent encountered problems in understanding some of the terminologies and pronunciation in English. A positive finding from the study revealed that majority of the respondents was well prepared before each lesson as indicated by 80% or 57 of the respondents. Finally, respondents were of the opinion that they were ready to teach both the subjects in English as indicated. In addition, it can be implied that some Mathematics and science teachers should be given motivational training to upgrade their proficiency in English Language. Based on the findings which only involved sixty-nine Mathematics and Science teachers, thus it is recommended that a larger study could be carried out with lager sample from the whole state of Sarawak that could provide a more valid and reliable information.Secondly, this study only concentrates on teachers' readiness, thus, it is appropriate to conduct a study that involves students' readiness too for both the primary and secondary schools. Finally, as this study only covered some aspects of technical training ICT for courseware for the respondents, it is recommended that a special study be conducted on teacher's training on handling of computer course wares in future to further enhance the process of teaching and learning Mathematics and Science in English.